The Importance Of Activating The Stock Of Skills By The Operating Agencies - Tindouf Branch - - Dene, Ahmed; Belghanami, Nadjat Wassila; Fardi, Hammad (جامعة الوادي - University of Eloued, 2020)
This study aims to identify the role of employment agencies and offices in activating the stock of skills in the local regions. We followed the descriptive analytical method and case method ,Both the questionnaire and the interview were used ; We reached the following results by testing hypotheses that employment agencies and offices of different types have had a clear impact on the activation of the skills inventory in the National Employment Agency (ANEM) of the Tindouf branch . The results of the correlation coefficients between all the axes of the study are strong, which indicates a strong level of influence of statistical significance, then acceptance of the hypothesis of the study.
مقال
Keywords: Stock of skills ; Employment Agency ; Labor Market ; Platforme ; Recruitment